Revolutionizing Education: Empowering Disaster Preparedness through Innovative Smart Teaching with e-Modules on FlipCreator Pro Platform - Erman Syarif; Abdul Malik; Alief Saputro; Hasriyanti Hasriyanti (Department of Geography Education, University of Jember, 2024)
Technology plays an important role to facilitate digital learning including to enhance students’ disaster preparedness. Therefore, teachers must be creative particularly for their course design. This study aims to develop smart teaching using e-modules with the FlipCreator Pro platform. We used Research and Development (R&D) with ADDIE model to develop e-modules involving experts and teachers to determine the validation of product. In additon, we measured students’ response towards quality of e-modules. Results show that developed e-moduls was adequate to validities, therefore it can be used to collected further data. The module's user-friendly design and practicality make it accessible and beneficial for students, promising improved comprehension and learning outcomes. Future research suggestions include expanding content, adapting for various grades, integrating AI, and conducting wider trials for generalizability. Examining the impact on student learning and teacher involvement is recommended for further exploration.